2002
DOI: 10.1159/000068546
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of human taste receptor genes belonging to the TAS2R family

Abstract: The sense of taste is a chemosensory system responsible for basic food appraisal. Humans distinguish between five primary tastes: bitter, sweet, sour, salty and umami. The molecular events in the perception of bitter taste are believed to start with the binding of specific water-soluble molecules to G-protein-coupled receptors encoded by the TAS2R/T2R family of taste receptor genes. TAS2R receptors are expressed at the surface of taste receptor cells and are coupled to G proteins and second messenger pathways.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
79
0
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(84 citation statements)
references
References 29 publications
0
79
0
5
Order By: Relevance
“…The nearly complete human and mouse T2R gene repertoires have been elucidated (Conte et al, 2002(Conte et al, , 2003Shi et al, 2003). Some valuable studies of Hu and Shi (2013) and Dong et al (2009) demonstrated the smallest bitter taste receptor (T2Rs) gene repertoire in carnivores and the dynamic evolution of bitter taste receptor genes in vertebrates, respectively.…”
Section: Phylogenetic Analysis Of T2r16 Amino Acid Sequences Of Foresmentioning
confidence: 99%
See 3 more Smart Citations
“…The nearly complete human and mouse T2R gene repertoires have been elucidated (Conte et al, 2002(Conte et al, , 2003Shi et al, 2003). Some valuable studies of Hu and Shi (2013) and Dong et al (2009) demonstrated the smallest bitter taste receptor (T2Rs) gene repertoire in carnivores and the dynamic evolution of bitter taste receptor genes in vertebrates, respectively.…”
Section: Phylogenetic Analysis Of T2r16 Amino Acid Sequences Of Foresmentioning
confidence: 99%
“…T2Rs are the largest family of taste receptors, which bind to tastants. Like olfactory and other chemosensory receptor genes, T2R genes also form a multi-gene family and display high sequence similarity (Conte et al, 2002;Shi et al, 2003). Coding regions of T2Rs contain an average of 300 codons, and they are not interrupted by introns, rendering them easy to be detected in whole-genome sequences.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2000, the T2R gene family (also known as TRBs or Tas2Rs) was identified and two mouse T2R genes were shown to be bitter taste receptors Chandrashekar et al 2000 ;Matsunami et al 2000) . To date, the complete T2R gene repertoires have been described in mammals, birds, amphibians, and some fishes (Conte et al 2002(Conte et al , 2003Go 2006 ;Shi and Zhang 2006) . In addition, a small number of T2R genes have also been described in several nonhuman primates (Parry et al 2004 ;Wang et al 2004 ;Fischer et al 2005 ;Go et al 2005) .…”
Section: T2r Gene Family -The More Variable Group Of Taste Receptorsmentioning
confidence: 99%